TRANSITION METAL COMPLEXATION WITH NAPROXEN AND EVALUATION OF THEIR IN VITRO ANTIMICROBIAL, CYTOTOXIC AND ANTHELMINTIC PROPERTIES - Hasan, Sharif; Begum, Farida (International Journal of Current Pharmaceutical Research, 2015)
Objective: The specific objective of this research was to synthesize transition metal complexes and investigate in vitro antimicrobial, cytotoxic and anthelmintic effects of naproxen and its complexes. Methods: Naproxen was complexed with copper, cobalt iron, silver and zinc and the characterization of these compounds were performed by proton NMR, FTIR, DSC, SEM, HPLC and elemental analysis. The antimicrobial activity was evaluated by disc diffusion method and cytotoxicity was evaluated by using brine shrimp lethality bioassay and compared with vincristine sulfate. The anthelmintic activity was evaluated against Pheritima posthuma. Results: Naproxen silver and zinc complexes showed potent activity while copper and cobalt complexes showed variable antimicrobial activity against some tested microorganisms. Naproxen iron complex showed moderate antimicrobial and very potent cytotoxic activity. According to these results we thought there might be any possibility to have anthelmintic properties on those complexes. However, we did not find any anthelmintic activity from them. Conclusion: The present study demonstrated that few naproxen metal complexes possess comprehensive antimicrobial and cytotoxic activities.